Benefits of alfalfa interseeding include reduced residual soil nitrate following corn production. Issue 3 (8th September 2021) - Osterholz, William; Ruark, Matthew D.; Renz, Mark; Grabber, John H.
Abstract: Interseeding alfalfa ( Medicago sativa L.) into corn ( Zea mays L.) silage can increase forage production, but the effects on soil nitrate pools remain unknown. We compared soil nitrate pools during and after interseeded alfalfa establishment in corn with pools during production of solo‐seeded corn followed by spring‐seeded alfalfa. Nitrogen (N) fertilizer was applied at three rates as a preplant broadcast or a 50:50 split between preplant broadcast and banded sidedress applications. During corn growth, soil nitrate levels from 0 to 30 cm were increased by higher N rates but were usually similar for both production systems. However, growth of interseeded alfalfa after corn harvest resulted in substantially lower residual fall and spring soil nitrate levels to a 90 cm depth, particularly under the highest N rate. Additionally, interseeded alfalfa influenced spring nitrate stratification by reducing nitrate in deeper horizons and increasing nitrate in the surface horizon. Interseeded alfalfa can thereby reduce the risk of nitrate leaching. Core Ideas:  Interseeding alfalfa may reduce environmental impacts of corn silage production.  Residual soil nitrate after corn harvest was reduced by interseeded alfalfa at both locations.  Greater N fertilizer rates increased soil nitrate during and after corn production.